Penentuan Harga Jual Kamar Pada Hotel Sederhana Di Kabupaten Berau - Siti Munawaroh (Jurnal Ekonomi STIEP, 2019)
The purpose of the research was to find out the basic price of Berau Regency sederhana hotel rooms using the Activity Based Costing System.The results of the calculation of the cost of the room using the Activity Based Costing System, which is for Deluxe room types of Rp. 323,472 for Grand Deluxe rooms of Rp. 329,052 and for Executive Suite rooms Rp. 329.90. there is a difference in price for a Deluxe room of Rp. 139,504, for a Grand Deluxe room of Rp.65,298, and for an executive suite a room of Rp. 31,423.